Tertiary Students Attitudes towards English Oral Communication Learning Outdoors: The Case of Indonesia - Rahman, Abd.; Novitasari, Devi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
While much research has documented university students attitude towards learning English oral communication skill in the classroom, their attitude to the learning of English oral communication skill outdoors has been under researched. To fill this gap, the present study aims to investigate university students attitudes to the learning of oral communication skill outdoors. Eight university students of English Department (4 males and 4 females) aged between 20-22 years old voluntarily participated in the study. Data of the study were gathered from informal interviews and students reflective writings carried out over the completion of tasks. The data were analyzed using attitudinal analysis system. The findings from affect aspect showcased students negative emotion to speak English outdoors. However, the result from judgement dimension showed that students were able to adapt to outdoor context; built their confidence; improve speaking skill, and engage in communication. The findings from appreciation aspects also showed positive trends that learning to speak English outdoors was engaging, authentic, and helpful to build students confidence. These empirical evidences suggest that learning to speak English outdoors promotes university students oral communication skill development in authentic and engaging ways.